Gontor and Community Economic Empowerment - Firmansyah, Irman (SMART Insight, 2024)
Pondok Modern Darussalam Gontor (PMDG) as a leading Islamic educational institution in Indonesia has proven its role not only focusing on religious education, but also on other aspects, namely social and economic, especially the economic empowerment of the people. This study looks at the role of PMDG in community economic empowerment. PMDG's economic empowerment is carried out through an integrative approach between education, entrepreneurship, and sharia-based and sustainable resource management. PMDG incorporates a modern curriculum that includes practical skills such as business management, agribusiness, and information technology in its learning. PMDG incorporates a modern curriculum that includes practical skills such as business management, agribusiness, and information technology in its learning. Thus, it succeeds in instilling entrepreneurial character among the santri, which in turn has an impact on the surrounding community. In addition, the economic programs also implemented by PMDG such as pesantren cooperatives, productive waqf and zakat, and ecology-based activities not only increase the independence of the institution, but also empower the surrounding community economically.